BLEEDING RECTAL VARICES IN A PATIENT WITH ETHYLIC LIVER CIRRHOSIS - A CASE REPORT - Grivcheva Stardelova, Kalina; Lichoska Josifovikj, Fana; Pislevski, Matej; Avramoski, Vladimir; Andreevski, Vladimir (SHMSHM - AAMD, 2022)
We present a rare case of a 60-year-old patient with established ethylic liver cirrhosis and bleeding rectal varices, treated with endoscopic ligation by placing 3 rubber bands consequently. These porto-systemic shunts can cause life-threatening bleeding due to their larger diameter and circulation. Although so far no standardized protocols for their treatment have been adopted, the method used to treat our case, after one month of monitoring, has proven to be a less invasive effective solution for reducing the risk of bleeding. Our aim was to illustrate one of the possible therapeutic approaches and to point out the importance of taking this complication into account in differential thinking in patients presenting with hematochezia.
Keywords: liver cirrhosis; rectal varices; endoscopic band ligation; portal hypertension